Analisis Pemberdayaan Petani Integrasi Kopi-Ternak Kambing dan Faktor-Faktor Yang Mempengaruhinya Di Kecamatan Simpang Empat Kabupaten Karo: Analysis Of Farmer Empowerment Through Coffee and Goat Farming Integration and Influencing Factors In Simpang Empat District, Karo Regency - Hotden Leonardo Nainggolan; Tongam Sihol Nababan; Yanto Raya Tampubolon; Wina Selvia Srimavolo Girsang (Universitas Wahid Hasyim, 2026)
This study aims to analyze the level of empowerment of coffee–goat integrated farmers and the factors influencing it in Simpang Empat District, Karo Regency, Indonesia. The research site was purposively selected due to its status as a coffee production center where farmers commonly integrate coffee farming with goat husbandry. A census sampling method was applied to 33 farmers who are members of farmer groups assisted by the Starbucks Farmer Support Center (SFSC). Primary data were collected through structured questionnaires and interviews, while secondary data were obtained from relevant institutions. Data were analyzed using descriptive statistics with a Likert scale to measure the Farmer Empowerment Index (FEI), and multiple linear regression to identify determinants of empowerment. The results indicate that farmer empowerment is categorized as strong to very strong, with the highest scores in decision-making ability (82.12%) and partnership and networking capacity (81.81%). Partially, farmers’ interest, participation, and the role of extension agents have a positive and significant effect on empowerment, with the role of extension agents emerging as the most dominant variable. Local culture shows a positive but statistically insignificant effect. Simultaneously, the regression model demonstrates strong explanatory power (R² = 0.716), indicating that 71.6% of the variation in empowerment is explained by the variables included in the model. These findings confirm that empowerment in integrated farming systems requires a systemic approach that combines individual capacity and institutional support to achieve sustainable agricultural development.